1970
DOI: 10.3329/bjsir.v45i2.5703
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bio-Oil from Municipal Solid Waste by Pyrolysis

Abstract: Municipal solid waste was pyrolyzed in a tubular reactor under vacuum. The effect of pyrolysis temperature and holding time on the product yields were investigated and the optimum conditions for pyrolysis were settled. The products of the pyrolysis were liquid pyrolytic oil, solid char and gaseous mixture. The pyro-oil was collected in a series of ice-cooled collectors. The uncondensed gas was blown off and the solid char was collected from the pyrolyser as a residue. The pyro-oil was then analyzed for fuel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Sarker et al [34] reported that large quantities of water was produced from the pyrolysis of waste polyethylene terephthalate (PET)-a polyesterbased plastic. The pH values of the liquid products ranged from 2.18 to 3.88, as expected from pyrolysis oils derived from biogenic-rich feedstocks [16,35,36]. In all cases, the primary condensates were more acidic (lower pH) than the secondary condensates, possibly due the presence of large amounts of water which diluted the latter liquid products.…”
Section: Effect Of Feedstock Moisture Content On Liquid Product Characteristicsmentioning
confidence: 72%
“…Sarker et al [34] reported that large quantities of water was produced from the pyrolysis of waste polyethylene terephthalate (PET)-a polyesterbased plastic. The pH values of the liquid products ranged from 2.18 to 3.88, as expected from pyrolysis oils derived from biogenic-rich feedstocks [16,35,36]. In all cases, the primary condensates were more acidic (lower pH) than the secondary condensates, possibly due the presence of large amounts of water which diluted the latter liquid products.…”
Section: Effect Of Feedstock Moisture Content On Liquid Product Characteristicsmentioning
confidence: 72%
“…In addition, pyrolysis and gasification of OFMSW are also promising methods [16] and result in the formation of valuable CO and H 2 -rich syngas, liquid, and solid residue (char) [17]. The obtained syngas can be used as a feedstock for methanol or Fischer-Tropsch synthesis [18], while the liquid product can be used as an alternative hydrocarbon source for fuel and other high-value chemical production [19], i.e., pyrolysis and gasification can contribute to the reduction of landfilled waste providing a better waste treatment option [20] and alternative energy production at the same time [21]. Due to the abovementioned reasons, this treatment of MSW gained significant attention among researchers in the past years and several scientific papers and reviews have been made in the topic of pyrolysis and gasification [22].…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al. [ 24 ] experimented with extracting pyrolytic oil from municipal solid waste at 400–550 °C, in which cellulosic biomass (organic food waste) was the primary raw material. The authors used scrap tires, waste paper, and plastic in an externally heated feed reactor pyrolysis system and analyzed and compared the pyrolytic fuel properties with petroleum-based oil.…”
Section: Introductionmentioning
confidence: 99%